The dynamic interactions of economic growth, foreign direct investment, and exchange rates in Ghana - Benedict Arthur; Bismark Addai (Cogent Economics & Finance, 2022)
This study examines the dynamic interactions among foreign direct investment (FDI), economic growth (GDPG), and real exchange rate (RER) in Ghana using time series data over the period 1996 to 2018, and two econometric models: a trivariate VAR and the ARDL bound test. The results reveal that no long-run relationship exists among the variables. However, a positive causal shock flows from both FDI and RER to GDPG. Also, the response of FDI to the shock in RER is positive. Therefore, it is recommended that the government implements policies that will ensure optimal balance in this nexus since a close and inter-reliant link exists among the variables.
Keywords: E22; E43; E52; F21; 330; ARDL bound test; Economic growth; exchange rate; FDI; trivariate VAR